The Effect of Timing of Intracranial Pressure Monitor Placement in Patients with Severe Traumatic Brain Injury. (16th November 2020) - Hoffman, Haydn; Bunch, Katherine; Protas, Matthew; Chin, Lawrence S
Abstract: INTRODUCTION: Intracranial pressure (ICP) monitor placement is indicated for patients with severe traumatic brain injury (sTBI) to minimize secondary brain injury. There is little evidence to guide the optimal timing of ICP monitor placement. METHODS: A retrospective cohort study using the National Trauma Data Bank (NTDB) from 2013 to 2017 was performed. The NTDB was queried to identify patients with sTBI who underwent external ventricular drain or intraparenchymal ICP monitor placement. Propensity score matching was used to create matched pairs of patients who underwent early compared to late ICP monitor placement using 6-hour and 12- hour cutoffs. The outcomes of interest were in-hospital mortality, non-routine discharge disposition, total length of stay (LOS), intensive care unit (ICU) LOS, and number of days mechanically ventilated. RESULTS: A total of 5, 057 patients with sTBI were included in the study. In-hospital mortality for patients with early compared to late ICP monitor placement was 33.6% and 30.4%, respectively ( P  = .049). The incidence of non-routine disposition was 92.6% in the within 6 hour group and 94.4% in the late placement group ( P  = .037). Hospital LOS, ICU LOS, and number of days mechanically ventilated were significantly greater in the late ICP monitoring group. Similar results were seen when using a 12- hour cutoff for late ICP monitor placement. In the Cox proportional hazards model, craniotomy (HR 1.097, 95% CI 1.037 - 1.160) and isolated intracranial injury (HR 1.128, 95% CI 1.055 - 1.207) were associated with early ICP monitor placement. Hypotension was negatively associated with early ICP monitor placement (HR 0.801, 95% CI 0.725 - 0.884). CONCLUSION: Despite a statistically marginal association between mortality and early ICP monitor placement, most outcomes were superior when ICP monitors were placed within 6 or 12 hours of arrival. This may be due to earlier identification and treatment of intracranial hypertension.